Pengaruh Konsentrasi Substrat Tepung Limbah Brem dan Lama Fermentasi Terhadap Produksi Kalsium Sitrat dengan Menggunakan Aspergillus niger ATCC 16404. - Agus Darmataba, Gusti Putu; Semadi Antara, Nyoman; Ganda Putra, G.P. (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 5 No 1 (2017): Maret)
Dregs brem is a waste of manufacture brem,  from basic materials are made  to be brem, only about 75% has managed to become brem while the remaining 25% to waste, brem waste still contains 10% sugar and starch by 12%. This research was done to  determine the effects  of substrate concentration and fermentation time on the  production of calcium citrate from waste brem by using Aspergillus niger. The research was experimental research, using a randomized block design factorial design, consisting of two factors. The first factor is the substrate concentration (25%, 30% and 35%), the second factor was the fermentation time (3, 5, and 7 days). The results showed that the concentrations of substrate and fermentation time very significant effect on the level of  calcium citrate, total soluble  solids and acidity (pH). The interaction of both  treatment effect was not significant on the level of calcium citrate, total soluble  solids and acidity (pH) fermented flour waste brem using Aspergillus niger. The average value is highest Ca-citrate in the treatment of substrate concentration of 30% amounting to 4.38 g/L and fermentation time 5 days amounted to 4.76 g/L. [Keywords]:  Aspergillus niger, flour waste Brem, substrate concentration, time of fermentation, calcium citrate
Keywords: 129,